2004
DOI: 10.1086/380450
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Blood Plasma Polymerase Chain Reaction for Management of Disseminated Adenovirus Infection

Abstract: We evaluated the usefulness of quantifying blood plasma adenovirus DNA loads for the management of adenovirus infection. Quantification of adenovirus A, B, and C DNA loads was done with real-time polymerase chain reaction (PCR) assays. Blood plasma specimens obtained from 44 immunocompromised patients were screened prospectively with this method. PCR findings for 36 patients were negative, and none of the patients developed disseminated adenoviral disease. PCR findings for 8 patients were positive; all 8 had i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
160
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(170 citation statements)
references
References 26 publications
(48 reference statements)
3
160
0
7
Order By: Relevance
“…Current antiviral agents are often limited by weak activity against adenovirus and by side effects, including suppression of bone-marrow function and renal toxicity (Bordigoni et al, 2001;Gavin & Katz, 2002;Ljungman et al, 2003;Lankester et al, 2004;Leruez-Ville et al, 2004).…”
mentioning
confidence: 99%
“…Current antiviral agents are often limited by weak activity against adenovirus and by side effects, including suppression of bone-marrow function and renal toxicity (Bordigoni et al, 2001;Gavin & Katz, 2002;Ljungman et al, 2003;Lankester et al, 2004;Leruez-Ville et al, 2004).…”
mentioning
confidence: 99%
“…As cidofovir had a broader range of activity against different HAdV types and clinical isolates, a multitude of case reports and noncontrolled studies on its use have been published. Although both recovery and treatment failures have been reported for both cidofovir [1][2][3]16,17] and ribavirin [3,4], more clinical experience has been gained with cidofovir. CMX001, a prodrug of cidofovir, has a higher in vitro activity against HAdV and is less nephrotoxic than cidofovir.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Another study identified high peak HAdV loads before treatment and a longer interval between onset of symptoms and start of therapy as risk factors for failure of cidofovir therapy [17].…”
Section: To Treat or Not To Treatmentioning
confidence: 99%
See 1 more Smart Citation
“…Cidovovir has been shown to have in vitro activity against all adenoviral serotypes 3 and data suggests an antiviral effect in certain treated individuals. 4 In contrast, Ribavirin appears to have in vitro activity primarily against subgroup C viruses 3 and this factor may contribute to the limited data supporting the antiviral efficacy of Ribavirin in vivo. 5 In addition to existing antiviral strategies, adoptive immunotherapy using cytotoxic adenovirus-specific T-cells may be a promising future therapeutic alternative.…”
mentioning
confidence: 99%